Transforming Agriculture into Energy: Unlocking Ukraine’s Bioenergy Potential for Sustainable Post-Conflict Recovery - Sergiusz Pimenow; Olena Pimenowa; Lubov Moldavan; Liudmyla Udova; Mirosław Wasilewski; Natalia Wasilewska (Energies)
Amidst the growing challenges of climate change, the advancement of bioenergy in Ukraine emerges as a strategic imperative for achieving sustainable development, energy independence, and compliance with international climate commitments. As one of the key pillars of Ukraine’s economy, the agricultural sector holds vast potential for renewable energy production, utilizing both crop residues and dedicated energy crops. This study provides a comprehensive assessment of the current state and potential of agrobiomass, taking into account the destruction of infrastructure and the urgent need for soil restoration. The novelty of this research lies in its in-depth evaluation of Ukraine’s bioenergy potential under conditions of energy system destabilization and in the introduction of innovative solutions aimed at strengthening sectoral resilience. The findings highlight the critical importance of expanding bioenergy production while identifying key institutional and regulatory barriers that hinder its progress. This study proposes actionable strategies to overcome these challenges, including the adaptation of international best practices, regulatory framework enhancements, and the implementation of targeted government support programs. The insights are valuable not only for policymakers in Ukraine but also for other countries striving to accelerate the transition to renewable energy and establish sustainable decentralized energy systems. Future research directions include the development of cutting-edge biomass processing technologies, a thorough economic evaluation of bioenergy’s long-term impact on energy and environmental sustainability, and an in-depth exploration of bioenergy’s cross-border potential to enhance the energy security and resilience of the European Union.